The Effect of Return on Assets on Stock Prices with Return on Equity as a Moderating Variable : Penelitian - Hari Ujiantara; Saefudin Zuhri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is quantitative with an explanatory approach, an approach that relies on hypothetical expectations based on previous research. The data used in this study is secondary data obtained by the researcher from manufacturing companies listed on the Indonesia Stock Exchange from 2019-2024. The data obtained by the researcher was analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the hypotheses used in this article can be accepted and proven. The first row of the third table above shows that the P-values ​​are positive and below the 0.05 significance level, namely 0.015. These results align with the research of Ajeng Syuhada Alawiyah (2022); (Khoirul Adzman 2021); (Amanda 2024) & (Sania 2022). The row below also shows a similar color, namely that the Return on Equity variable can moderate the effect of the Return on Assets variable on the stock price variable due to the same reason, namely the P-values ​​are positive and below the 0.05 significance level, namely 0.000. Thus, it can be concluded that the first and second hypotheses in this article can be accepted and proven.